Genome-wide association analysis of type II resistance to Fusarium head blight in Pakistani spring wheat germplasm - Ullah, Rafi; Khan, Fahim Ullah; Ullah, Inam; Spanic, Valentina; Budimir, Katarina Sunic; Rehman, Attiq ur (Springer Nature, 2025)
Fusarium head blight (FHB) is a devastating fungal disease of wheat, causing significant losses in grain yield and quality. Understanding the genetic basis of FHB resistance is crucial for developing resistant varieties. This study aimed to characterize the genetic architecture of FHB resistance in a diverse panel of Pakistani spring wheat germplasm, consisting of 150 recognized varieties, 45 landraces/lines, and two check varieties. Resistance to fungal spread along the spike (Type II resistance) was evaluated under controlled conditions, and the genotypes were categorized based on FHB scores ranging from 0 (highly resistant) to 9 (highly susceptible). We found statistically significant variation (p ≤ 0.01) for resistance to type II FHB in the tested panel including some promising genotypes with high levels of resistance to the infection. To dissect the genetic basis of FHB resistance, multi-model GWAS were performed using 14,800 SNP markers from the 50 K SNP array. Population structure and kinship were accounted for to control false positives, using principal components and a kinship matrix. Our study identified eight quantitative trait loci (QTL) regions associated with Type II FHB resistance, distributed across six chromosomes (1A, 1B, 2A, 2B, 7B, and 7D). Among these, q_Fhb_1B on chromosome 1B was consistently detected across multiple models, underscoring its potential as a key resistance locus based on the top SNP 1B_667978743. Haplotype analysis further revealed favorable allele combinations linked to resistance, providing additional insights for marker-assisted selection. These findings offer valuable insights for genome-based breeding strategies aimed at enhancing FHB resistance while maintaining agronomic performance, thereby contributing to the development of more resilient wheat varieties suitable for FHB-prone regions.
Keywords: Fusarium head blight; Spring wheat; QTL; GWAS; Type II resistance; MAS